Vpogled v latinsko ustvarjalnost na Slovenskem od obdobja reformacije do prve polovice 19. stoletja - Hriberšek, Matej (Jezik in slovstvo, 2020)
Latin literary creation in Slovenia is a relatively poorly researched field in this country, as it has been dealt with by only a few researchers. In the study of Slovenian literary history, too, there are authors who exclusively or at least partly wrote in the Latin language and who are frequently either overlooked or marginalised, thus leaving a significant gap in the understanding and evaluation of their work. A large proportion of literary authors had a classical education and, through their education, both classical languages often left a noticeable mark on their output, both in the topics of their works and in their language. Thus, a thorough overview of Latin creativity in Slovenia still remains a desideratum not only in the field of philology, but also of Slovenian studies and numerous other fields. The present article concisely presents Latin creativity in Slovenia from the mid-sixteenth to the mid-nineteenth century, while some of its fields are also accompanied by illustrative examples.
Keywords: 16./19. st.; 16th/19th cent.; Latin; latinščina; literarne zvrsti; literary genres; manuscripts; Neo-Latin literature; novolatinska književnost; rokopisi; Slovenia; Slovenija